Truth in visual media : aesthetics, ethics and politics - La Caze, Marguerite; Nannicelli, Ted (Edinburgh : Edinburgh University Press, 2021)
Shows how aesthetic, ethical, and political questions intersect in a range of art forms as found in traditional media.
Introduction / Marguerite La Caze and Ted Nannicelli -- Part one. Aesthetics -- 1. Repair and the irreparable in contemporary Aboriginal Art / Susan Best -- 2. Circulating bodies : retelling the trauma of the Algerian War through photography and art / Amy L. Hubbell -- 3. An i for an eye : the collective shaping of experience in the Age of Machine-Mediated Art / Ellen Marie Saethre-McGuirk -- Part two. Ethics -- 4. The ethics of filmmaking : how the genetic history of works affects their value / Mette Hjort -- 5. The Look of Silence and the ethics of atonement / Marguerite La Caze -- 6. Truth, performance and the close-up : paradoxical candour in Errol Morris's 'Interrotron' interviews / Robert Sinnerbrink -- 7. Mindhunter : the possibility of knowing evil / Damian Cox -- Part three. Politics -- 8. Interactive documentary, narrative scepticism and the values of documentary film / Ted Nannicelli -- 9. Won't somebody please think of the children! On the moralisation of video game violence / Grant Tavinor -- 10. Re-reading personal influence in an Age of Social Media / Tom O'Regan -- 11. Principles of exchange : free speech in the era of fake news / Kris Fallon.
Includes bibliographical references and index.
JSTOR
Keywords: Truth in mass media; Mass media -- Moral and ethical aspects; Art -- Moral and ethical aspects; Art -- Political aspects; Truth; Imagery (Psychology); Imagery (Psychology) -- In mass media; Imagery, Psychotherapy; Médias -- Aspect moral; Art -- Aspect moral; Art -- Aspect politique; Vérité.; Imagerie (Psychologie); Imagerie (Psychologie) -- Dans les médias.; political art; truth; imagery; Art -- Moral and ethical aspects; Art -- Political aspects; Imagery (Psychology); Mass media -- Moral and ethical aspects; Truth